2020
DOI: 10.31348/2020/22
|View full text |Cite
|
Sign up to set email alerts
|

External Ophthalmomyiasis Caused by Oestrus Ovis (A Case Report)

Abstract: The work deals with atypical conjunctival infection of Czech patient with Oestrus ovis larvae. Ophthalmomyiasis is infestation of mammalian eyes by the larvae or worms of some flies. The most common cause of human myiasis is the Sheep. Shepherds are infected in habitats, but human eye disease outside the areas of abundant hamsters is rare. We describe a case of eye disease in a middle-aged man from the Czech Republic who spent a summer holiday seven weeks before examination in the north of Greece. During the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Pupic-Bakrac et al [12] published 2 cases from Croatia in 2020 and believe that global warming and climate change may increase the prevalence of O. ovis . In the same year, Hartmannova et al [5] reported a case from Czech Republic, where ophthalmomyiasis is only rarely seen in ophthalmology departments. Atypically, their patient presented to the clinic only 7 weeks after a possible contact while traveling Greece and more than 20 larvae were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pupic-Bakrac et al [12] published 2 cases from Croatia in 2020 and believe that global warming and climate change may increase the prevalence of O. ovis . In the same year, Hartmannova et al [5] reported a case from Czech Republic, where ophthalmomyiasis is only rarely seen in ophthalmology departments. Atypically, their patient presented to the clinic only 7 weeks after a possible contact while traveling Greece and more than 20 larvae were found.…”
Section: Discussionmentioning
confidence: 99%
“…People working with these host animals or spending their time close by are more prone to infestation, which can happen either by contaminated hands or direct encounter with the adult female fly. However, the condition is not only reported in rural areas with farmers or animal husbandry but also by accidental encounter in people from all over the world and even urban areas without direct or close contact to animals [3][4][5][6][7][8]. We present the case of a 23-year-old female with ophthalmomyiasis externa due to O. ovis larvae observed in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Talks and Wölfelschneider and Wiedemann describe two cases where O. ovis infestation occurred following a vacation to Rhodes 7 8. Fries et al describe a case in a travelling climber on another Greek island who had extensive contact with sheep,9 while Hartmannová et al describe a case contracted in northern, mainland Greece 10. Other than the case described by Fries et al, there were no reports of extended animal contact.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrus ovis (Linneo, 1761) (Diptera, Oestridae), also known as the sheep botfly, is an obligate parasite whose larvae cause cavitary myiasis in small ruminants (Alcaide et al, 2005; Uslu and Dik, 2006b; Dönmez et al, 2006; Angulo‐Valadez et al, 2010; Attia et al, 2019). Oestrosis mainly affects sheep and goats, but accidental nasal, pharyngeal and ocular infestations have been reported in other species such as dogs ( Canis lupus familiaris ) (Zanzani et al, 2016) and in humans, typically in shepherds and farmers (Hartmannová et al, 2020). Larval migration causes constant irritation, and difficulty breathing and feeding (Dorchies et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Oestrosis mainly affects sheep and goats, but accidental nasal, pharyngeal and ocular infestations have been reported in other species such as dogs (Canis lupus familiaris) (Zanzani et al, 2016) and in humans, typically in shepherds and farmers (Hartmannová et al, 2020). Larval migration causes constant irritation, and difficulty breathing and feeding (Dorchies et al, 1998).…”
Section: Introductionmentioning
confidence: 99%